Painful Elastofibroma Dorsi: A Report of a Case and a Brief Review of the Literature - Evangelos Falidas; Dimitrios Arvanitis; Georgios Anyfantakis; Angelos Pazidis; Zacharoula Koukouli; Dimosthenis Miltiadou; Anastasia Koronaiou (Case Reports in Orthopedics)
Elastofibroma dorsi (ED) is an uncommon, slow-growing, benign, soft tissue tumor of unclear pathogenesis, typically located at the subscapular region of elderly people. It may be unilateral or bilateral. Though many patients are asymptomatic, ED can cause local deformity and symptoms such as periscapular pain or discomfort. Herein we report a case of a 65-year-old woman with painful ED. Clinical features, radiodiagnostic, intraoperative, and pathologic findings, and a brief review of the literature are performed.